Half-hard cast-iron rolls: statistically research on the manufacturing technology for increase their quality and safety in exploitation. Issue 1 (February 2021) - Kiss, I; Alexa, V; Cioată, V G; Ratiu, S
Abstract: The regression analysis provides an opportunity to specify hypotheses concerning the quality assurance of cast-iron rolls, as well as explanatory factors in their manufacturing practice. When the analysis is correctly executed, having on base the statistically valid adjustment, this can produce quantitative effects on the quality assurance process. In the practice of the rolling rolls manufacturing by casting many variables interact with each other simultaneously (the iron properties, the casting equipment and they execution, the casting temperature, the cooling and solidification and so on). Multivariate research and visualization comes to the fore when the engineers have difficulties in comprehending many dimensions at one time, especially in the iron melting and alloying stages. In order to establish the optimal condition for hardness assurance in the cast-iron rolls manufacturing we proposed a statistical modelling study by using the multivariate regression. Our research propose to analyse the half-hard cast-iron rolls, an analysis defined by the statistically analyse of the cast rolls manufacturing technology, using the modelling phenomenon and the mathematical approach. The optimization model is based on industrial data, obtained from half-hard cast-iron rolls. Their analysis shall lead to the optimization pattern, through the prism of the multicomponent correlations, expressed by mathematical formulae.